Antibiotic and Heavy Metal Resistance Profiles of Staphylococcus aureus Isolates from Hospitals - Siriwong, Nitipong; Chukeatirote, Ekachai (Acta medica Lituanica, 2026)
Background: Staphylococcus aureus is a major opportunistic pathogen in hospitals, where sustained exposure to antimicrobial agents and disinfectants promotes the emergence and persistence of resistant strains. In addition, tolerance to heavy metals may facilitate co-selection and long-term survival of resistant S. aureus in clinical settings.Purpose: This study investigated the occurrence of methicillin-resistant S. aureus (MRSA), vancomycin-intermediate S. aureus (VISA), and vancomycin-resistant S. aureus (VRSA), and evaluated antibiotic and heavy metal resistance profiles among S. aureus isolates recovered from hospitals.Materials and Methods: Seventy-nine bacterial isolates were collected from three hospitals. Identification using Gram staining and biochemical tests identified 71 S. aureus isolates. Resistance to antibiotics was determined by disk diffusion, and was quantified using the multiple antibiotic resistance (MAR) index. Resistance to heavy metals was assessed at increasing concentrations, and the multiple heavy metal resistance (MHMR) index was calculated. MRSA, VISA, and VRSA were screened using selective agar containing oxacillin and vancomycin. Cluster analysis was performed based on combined antibiotic and heavy metal resistance profiles.Results: High resistance rates were observed for penicillin and ampicillin (95.8% each), whereas most isolates showed low levels of resistance to chloramphenicol, bacitracin, streptomycin, kanamycin, and methicillin. MAR index values ranged from 0 to 0.88, with most isolates exceeding 0.2. All isolates exhibited resistance to multiple heavy metals, with MHMR values between 0.57 and 0.71, and marked tolerance to chromium and lead. Screening identified 9 MRSA, 3 VISA, and 1 VRSA isolate, including one strain classified as both MRSA and VRSA. Cluster analysis resolved nine major resistance-associated groups.Conclusion: Hospital-associated S. aureus isolates showed extensive antibiotic and heavy metal resistance, supporting the likelihood of co-selection of resistance traits. These findings underscore the importance of integrated antimicrobial stewardship and environmental control strategies in hospitals.
Keywords: antibiotic resistance; heavy metal resistance; Staphylococcus